Frictions and approaches to art teaching in early childhood education: teacher formation and contemporary art (Palíndromo, 2022)
The article analyzes, from a historical-cultural perspective, issues relevant to the initial training of teachers of the Licentiate Degree in Visual Arts – Integral (2006 version), at the Federal University of Espírito Santo – UFES, and how this training reverberates in the ways of teaching contemporary art in early childhood education, which, in times of significant technological advances, has redimensioned the way children produce and consume art. Therefore, it carries out a case study based on interviews and dialogues with teachers in this segment of basic education. It is based on Vigotski (2007) to address the cultural-historical perspective in the field of psychology, on Bakhtin (2010)), in the field of language, and on Benjamin (2007) to think about children. In the field of art education, it draws on Barbosa (2005) and Cocchiarale (2006) and, for teacher education, on Fonseca da Silva (2019), Foerste and Camargo (2019) and Nóvoa (2009). It ends by proposing an approximation between the training of teachers and contemporary art, presenting educational proposals based on a contemporary teaching of art for young children.
Keywords: Teacher training; Child education; Art education; Contemporary art